MRI diagnosis of ovarian fibrothecomas: tumour appearances and oestrogenic effect features - Wu, B (The British Institute of Radiology., 2014)
OBJECTIVE: To study MRI diagnosis of ovarian fibrothecomas. METHODS: MRI appearances of 27 ovarian fibrothecomas 26 female patients confirmed by surgical pathology were retrospectively reviewed and correlated with clinical and histological findings. RESULTS: Most patients were post-menopausal females 73.1% (19/26) of cases. 38.5% (10/26) of patients showed an elevated serum carbohydrate antigen 125 (CA-125) level (>35 U ml(−1)). On MR T(2) weighted imaging, 3 distinct features were revealed. (1) Homogeneous hypointense masses in 25.9% (7/27) cases. (2) Heterogeneous tumours with mostly isointense and few patchy hyperintense areas in 51.9% (14/27) cases. (3) Heterogeneous tumours with predominantly hyperintense and few isointense parts in 22.2% (6/27) cases. On T(1) weighted imaging, all the fibrothecomas turned out to be homogeneous masses except six cystic degeneration cases. After contrast, 70.4% (19/27) tumours showed homogeneous mild enhancement in all phases. Beyond the tumours, endometrial abnormality and uterus enlargement were found in 38.5% (10/26) and 15.4% (4/26) patients, respectively. Ascites were seen in 53.8% (14/26) patients. There was a statistically significant difference among the 3 T(2) weighted image features (F = 7.024; p = 0.003) in terms of the size of fibrothecomas. The cystic tumours also had the tendency to show the ascite condition (p = 0.002) as well as elevated serum CA-125 levels (p = 0.014). Vimentin was positively stained in 10 (76.9%) of 13 cases who underwent the immunohistochemical analysis. CONCLUSION: MRI has the superiority to show the distinct appearances of tumours as well as their functional features according to oestrogenic effect. ADVANCES IN KNOWLEDGE: This study describes the unique features of fibrothecomas on MRI on a relatively large series of patients with tumours and the indirect oestrogenic effect findings.